Integrating interaction with agents, environment, and organisation in JaCaMo. (2016) - Zatelli, Maicon Rafael; Ricci, Alessandro; Hübner, Jomi Fred
Interaction is a subject widely investigated in multi-agent systems (MASs), but some issues are still open. While most of current approaches of interaction in MAS just consider the interaction among agents, some problems are better modelled when the interaction exploits the synergy with agents, environment, and organisation. In this paper, the interaction is conceived as a first-class abstraction considering the other MAS components, like the organisation and the environment. The main aim is to exploit the synergy among the interaction and the other MAS components, where a MAS developer benefits from the advantages of specifying, developing, and executing the interaction component as a first-class abstraction. The paper presents a conceptual model for the interaction component, a language to define the interaction, the integration of the interaction component into the JaCaMo platform, and an evaluation of its benefits and drawbacks.